In Vitro Evaluation of Trichoderma asperellum Isolate UGM-LHAF against Rhizoctonia solani Causing Sheath Blight Disease of Rice - Yeyet Nurhayati; Suryanti Suryanti; Arif Wibowo (Jurnal Perlindungan Tanaman Indonesia, 2021)
Trichoderma spp. is a fungus widely used to control soil-borne pathogens, such as Rhizoctonia solani which is plant pathogenic fungi in widely host range, especially on rice. This research aimed to evaluate the ability of Trichoderma asperellum isolate UGM-LHAF against R. solani causing sheath blight disease of rice in vitro condition. Trichoderma sp. used in this research was obtained from The Biological Laboratory of Pakem, Yogyakarta, Indonesia, and Rhizoctonia sp. was obtained through isolation of diseased rice obtained from rice fields in Yogyakarta. The two isolates were characterized base on morphology and molecular identification based on ITS rDNA. The pathogenicity test of Rhizoctonia sp. was evaluated by adding four sclerotia of Rhizoctonia sp. near rice roots at 6 days after sowing. The in vitro test used dual culture and antifungal activity (0%, 10%, 25%, 50% culture filtrate of Trichoderma sp.) with three replicates of each treatment. Two isolates were identified as T. asperellum and R. solani. Sheath blight symptoms appeared after 12 days inoculation. In the in vitro test, T. asperellum isolate UGM-LHAF was able to inhibit the mycelial growth of R. solani (64.23% on dual culture and 68.5% on antifungal activity). This study suggests that T. asperellum isolate UGM-LHAF able to inhibit the growth of R. solani and can be a further potential candidate as a biocontrol agent against R. solani causing sheath blight disease of rice.